Applicability of Flow Resistance Formulae for Sand-Bed Channels: An Assessment Using a Very Large Data Set - Peng, Hao; Huang, He Qing; Yu, Guoan; Zhang, Hongwu (Frontiers in Environmental Science, 2022)
Among numerous flow resistance formulae for sand-bed channels, this study selects five for evaluation and in order to cover flow conditions in sand-bed river channels as widely as possible, 1636 sets of field measures are collected from the hydrological stations in two large river systems of China - the Yellow and Yangtze Rivers, in addition to the data compiled by Brownlie. The performance of the selected formulae in yielding the values of Manning resistance coefficient n is evaluated against total 6,805 data sets. In many cases, Ma et al. formula yields unreasonable n values of <0, while Deng et al. formula and Formulas 1 and 2 of Zhang et al. yield n values varying beyond the range of 2:1 to 1:2. Wu and Wang formula yields n values varying within the scope only in the cases of n<0.04. By dividing ARE from the selected formulae into six groups of 0-0.05, 0.05 to 1, 0.1 to 0.2, 0.2 to 0.5, 0.5 to 1, and >1, it can be found that for all five selected formulae, ARE occurred in the group of 0.2-0.5 occupy the largest percentage, while each of the adjacent groups of 0.5-1 and 0.1-0.2 occupies also a very large percentage. Hence, all five formulae must improve their predicting abilities.